(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: As a global public health recommendation, infants should be exclusively breastfed for the first six months of life to achieve optimal growth, development and health. Thereafter, to meet their evolving nutritional requirements, infants should receive nutritionally adequate and safe complementary foods after 6 months of their age while breastfeeding continues for up to two years of age or beyond. Objective: To find out the pattern of breastfeeding, pre-lacteal feeding and complementary feeding practices among the mothers of 06 months to 3 years old children in a selected rural area. Material and Methods: This descriptive cross-sectional study was conducted among 390 rural mothers from selected villages of Manikganj and Dhaka district from October to December 2016. Data were collected through face-to-face interview with a preformed semi-structured questionnaire. Result: Among 390 mother only 44.8% started breastfeeding within an hour of child birth. Pre-lacteal feeding practice was very high (70.4%) and 36.7% mother fed their baby with infant formula. The duration of exclusive breastfeeding was variable; about 49.7 % of children were exclusively breastfed for 5-6 months. Among the variety of foods, most common complementary foods include suji (20.1%), homemade hotchpotch (17.5%), natural cow’s milk (16.3%) and infant formula (16.1%). Conclusion: This study data suggest that delayed initiation of breastfeeding rate is high along with pre-lacteal feeding. An intensive program is needed create awareness among the rural mothers about exclusive breastfeeding and proper weaning. Journal of Armed Forces Medical College Bangladesh Vol.14(1) 2018: 62-65